Cryogenic machining performance of M303 at high cutting speeds - Nur Fadhilah Aimuni Mohd Ridzuan,; Tahrin Othman,; Afifah Zakiyyah Juri,; Jaharah A. Ghani,; Che Hassan Che Haron, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The material M303 is commonly used in the fabrication of machinery, automotive components, locomotive axle housings, and injection moulds. It is a stainless martensitic chromium steel known for its high strength, wear resistance, and corrosion resistance. The primary purpose of this study is to investigate the machinability of M303 under cryogenic conditions, specifically focusing on high cutting speeds. By exploring the effects of cryogenic machining on M303, the study aims to provide insights into the performance and characteristics of this material under extreme cutting conditions. This study investigates the influence of cutting parameters on the machinability of M303 in a cryogenic environment using liquid nitrogen (LN2) and coated carbide cutting tools in a high-speed turning process. The study focuses on high cutting speeds and examines essential machinability factors, including cutting forces, surface finish, and tool life. The experimental design utilises a Taguchi L4 orthogonal array to systematically study feed rates (0.1-0.2 mm/rev), depth of cut (0.2-0.6 mm), and high cutting speeds (260-340 m/min). Notably, at a low cutting speed of 260 m/min, coupled with low feed rates and depth of cut, the study reveals the longest tool life of 48.57 mintues was achieved. This condition is characterized by a good surface finish and low cutting forces with Ra of 0.9 μm and cutting force of 100 N respectively. The predominant wear occurs on the flank face, primarily due to fracturing and chipping, especially under high combinations of cutting parameters. Conversely, gradual wear is observed under low combinations of cutting parameters, resulting in an extended tool life. In conclusion, the application of LN2 proves effective under conditions of low cutting parameters. The study suggests that the risk of fracturing the cutting tool increases at higher feed rates and depths of cut, especially when combined with elevated cutting speeds. This research provides valuable insights into optimizing the machining of M303 for enhanced efficiency and tool longevity.